Accommodating the urban informal sector : a study of the integrated hawkers management program in Quezon City, Philippines - Reodique, Jason Estrada; Amin, A.T.M. Nurul; Weber, Karl E.; Sheng, Yap Kioe; Canadian International Development Agency (Bangkok : Asian Institute of Technology, 1988)
The proliferation of hawkers and sidewalk vendors ha s become a major problem for the city administrators of almost all Third World countries. There is a need for policy actions to abate if not totally eradicate them. This study, based on a n evaluation of the Integrated Hawkers Management Program in Quezon City, Philippines, determines the effectiveness o f this program which regulates hawking through the provision of flea markets. The program has delivered some benefits to the city government, the hawkers, and the consuming public, despite several short comings in its implementation. Through the ·program, the city revenue was increased by a bout P1. 025 million, the hawkers attained legitimate status, and an orderly place for marketing of goods ha vi n g demand is mad e available at t he convenience of the consuming public . However, it fell short of meeting the overall regulatory objectives. Several courses of actions such as expanding the scope of licensing, providing basic facilities in the flea markets, the regular monitoring of these areas, and extending credit are recommended to improve the program a nd achieve its goal of promoting self-employment in an orderly manner.
A Thesis Submitted in Partial Fulfilment of the Requirements for t he Award of the Degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1988
Keywords: Peddlers and peddling -- Philippines -- Quezon City